Environmental assessment effects of the antibiotic tylosin on biological properties of the chernozem ordinary - Sergey Ilich Kolesnikov; Kamil Shagidullovich Kazeev; Yuliya Viktorovna Akimenko; Mary Yurevna Odabashyan; Ksenia Nikolaevna Nikolaeva (Наука. Инновации. Технологии, 2022)
In model experiments the prolonged nature of action of a veterinary antibiotic tilosin (100, 300, 450, 600 mg/kg) and its complex with a fungicide antibiotic nystatin on micro-biocenosis and enzymatic activity of the chernozem ordinary is shown. The complete recovery of biological properties of the chernozem doesn’t occur and in 120 days.